Social Media Usage and Its Impact on Learning Habits of Bachelor in Elementary Education Student of Altavas College - Janniela A. De Pedro,; Charie Mae O. Geroy,; Rowena N. Rufo,; Dr. Mikko Jan D. Lopez, EdD (Scholars Digest Publishing, 2022)
The primary purpose of this study was to determine the level of social media usage and learning habits of all BEED students of Altavas College. The researchers collected the data by using an electronic web-based questionnaire through the Google survey tool (Google Forms) using questions modified from social media use and learning habits. The survey comprised 2 subsections according to the participant's social media use and a question correspond to each respondent's learning habits. Data gathered and analyzed by calculating manually. The result showed on the level of social media usage that the respondents were “Moderately Engaged". This signifies how the respondents stems largely in their own perspective and full growth on how to handle social media use since this is considered as one of the main factor affecting their ways of learning. The level of learning habits of Bachelor in Elementary Education of Altavas College was described as “highly practiced,”. It signifies that the respondents hold on how learning habits make their studies easier to understand and make their learning experience comfortable and enjoyable. The analysis perceived using the frequency count, percentage, and mean. Descriptive analysis were computed.
Keywords: Learning Habits, Social Media Usage, Utilized, Impact, Level.